Inovasi Pembelajaran Numerasi Melalui Pelatihan Augmented Reality Berbasis Assemblr EDU Bagi Guru Matematika - Dwi Novitasari; Sudi Prayitno; Amrullah Amrullah; Junaidi Junaidi; Deni Hamdani; M Khoirul Hafizin (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
Numeracy is a fundamental competency that should be developed through innovative mathematics learning. However, the use of digital technology by teachers to support numeracy learning remains limited. This community service program aimed to enhance the competencies of junior high school mathematics teachers in West Lombok Regency in developing and implementing numeracy learning through Augmented Reality (AR) using Assemblr EDU. The program involved 20 mathematics teachers who are members of the Mathematics Teachers Association (MGMP) of West Lombok Regency through training, media development practice, mentoring, and evaluation. The evaluation results showed that participants were able to independently develop AR-based learning media. A total of 95% of participants stated that the training materials met their needs, improved their skills in utilizing educational technology, and helped visualize abstract mathematical concepts in a more concrete and engaging way. In addition, 90% of participants expressed satisfaction with the implementation of the program. This activity contributed to strengthening teachers’ digital competencies and supporting the implementation of more innovative and interactive numeracy learning.